Dissection of Double-Stranded RNA Binding Protein B2 from Betanodavirus - Fenner, Beau J. (American Society for Microbiology, 2007)
Betanodaviruses are small RNA viruses that infect teleost fish and pose a considerable threat to marine aquaculture production. These viruses possess a small protein, termed B2, which binds to and protects double-stranded RNA. This prevents cleavage of virus-derived double-stranded RNAs (dsRNAs) by Dicer and subsequent production of small interfering RNA (siRNA), which would otherwise induce an RNA-silencing response against the virus. In this work, we have performed charged-to-alanine scanning mutagenesis of the B2 protein in order to identify residues required for dsRNA binding and protection. While the majority of the 19 mutated B2 residues were required for maximal dsRNA binding and protection in vitro, residues R53 and R60 were essential for both activities. Subsequent experiments in fish cells confirmed these findings by showing that mutations in these residues abolished accumulation of both the RNA1 and RNA2 components of the viral genome, in addition to preventing any significant induction of the host interferon gene, Mx. Moreover, an obvious positive correlation was found between dsRNA binding and protection in vitro and RNA1, RNA2, and Mx accumulation in fish cells, further validating the importance of the selected amino acid residues. The same trend was also demonstrated using an RNA silencing system in HeLa cells, with residues R53 and R60 being essential for suppression of RNA silencing. Importantly, we found that siRNA-mediated knockdown of Dicer dramatically enhanced the accumulation of a B2 mutant. In addition, we found that B2 is able to induce apoptosis in fish cells but that this was not the result of dsRNA binding.